Role of aquaporins in brain water transport and edema - Li, Yuyuan; Wang, Yining; Huang, Xingda; Zhang, Hao; Guan, Youfei; Zhang, Xiaoyan (Frontiers in Neuroscience, 2025)
Water serves as the primary substance in all living cells and is an essential molecule involved in numerous biological processes critical for maintaining homeostasis in the central nervous system (CNS). Disruptions in water balance can occur in conditions such as cerebral edema, where fluid accumulation results in increased intracranial pressure (ICP). Aquaporins (AQPs) are transmembrane proteins that play a vital role in the rapid transport of water across cell membranes. Various subtypes of AQPs (AQP1, AQP3, AQP4, AQP5, AQP6, AQP7, AQP8, AQP9, and AQP11) have been identified in brain tissue. This review summarizes the latest advancements in our understanding of the critical role of AQPs in regulating water transport in brain edema. Abundant evidence indicates that AQP4, the most prevalent AQP in the CNS, regulates brain water transport and contributes to both cytotoxic and vasogenic edema, suggesting that AQP4 may serve as a potential therapeutic target for brain edema. Additionally, some studies have indicated that AQP1 plays a significant role in the formation of cerebrospinal fluid (CSF) and the maintenance of steady-state ICP. However, to date, these findings have not been translated into clinical practice. There is an urgent need to develop specific AQP inhibitors and activators to explore the potential benefits of modulating the functions of AQP1 and AQP4 in the context of brain edema.